NASKAH PUBLIKASI PENGARUH RISIKO BISNIS, LIKUIDITAS, PERTUMBUHAN PENJUALAN, DAN STRUKTUR ASET TERHADAP KEPUTUSAN PENDANAAN DI MODERASI UKURAN PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2012-2016 - Firdaus Damas Septio Ardiansyah, 14.05.52.0260; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2018)
This study aimed to examines the influence of the business risk, liquidity, growth of sales, and asset structure on the funding decision moderated by company size. This research was conducted at Indonesia by using analysis unit property and real estate company that have gone public. The population of this research are property and real estate company that listed in Indonesia Stock Exchange. The sampling method using purposive sampling with the study period of 2012 until 2016 and obtained as many as 84 companies. The technique of data analysis is used multiple regression analysis with interation method. The results of this study shows that business risk and liquidity does not affect on funding desicion. The growth of sales significant positive influence on funding desicion. The asset structure significant negative influence on funding desicion. Moderating testing firm size showns that firm size is not proven as moderating variable that can strengthen or weaken the relationship liquidity on funding desicion. While, moderating testing firm size showns that, firm size proved weaken the relationship of the growth of sales on funding desicion,as well asÂ the influence of asset structure on funding desicion can be strengthened by firm size.Keywords: The Business Risk, Liquidity, Growth of Sales, Asset Structure, Firm Size, and Funding Decision